Persepsi Konsumen pada Konten IGC dan FGC di Akun Instagram @meccafriedchicken.id - Nagiza Akbar; Jefri Audi Wempi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to understand the engagement rate (ER) gap between Influencer Generated Content (IGC) and Firm Generated Content (FGC) on the Instagram account @meccafriedchicken.id in September 2025 through consumer perceptions. This study uses a descriptive method with a descriptive qualitative approach and a constructivist paradigm. Research data were collected through literature studies, text observations of the Instagram account @meccafriedchicken.id, and semi-structured in-depth interviews with external and internal informants, as well as specialists. The results show that the reason behind the ER gap is that consumers find IGC more appealing because it combines visual and audio stimuli simultaneously. Therefore, consumer perceptions are formed through the visual appearance of the product, the influencer's communication style, and the comprehensive delivery of information. This study concludes that content type and influencer presence significantly influence the process of forming consumer perceptions of a brand on social media